Lease Agreement of "Surat Ijo" Land in Surabaya in Relation to Law Number 5 of 1960 on the Basic Agrarian Law - Saleh, Moh.; Firmansyah, Alfian Ramadhan (Jurnal Hukum dan Keadilan, 2025)
This journal examines the legal implications of lease agreements involving "Surat Ijo" land in Surabaya in the context of Law Number 5 of 1960 on the Basic Agrarian Law (UUPA). "Surat Ijo" is a type of land document in Indonesia that holds significant legal standing for land ownership and usage rights. The study aims to explore how lease agreements concerning "Surat Ijo" land align with the UUPA's regulations, specifically addressing the issue of land rights, legal certainty, and the protection of both lessors and lessees. Through a normative juridical approach, the research highlights key legal provisions in the UUPA that govern land use, transfer, and lease, and discusses their relevance to "Surat Ijo" land transactions in Surabaya. The analysis reveals the complexities surrounding the lease of such land, particularly concerning its long-term leaseability, legal risks, and the need for clearer regulations to ensure the protection of parties involved. The journal concludes with recommendations for improving legal clarity and the enforcement of land rights to strengthen the legal framework surrounding "Surat Ijo" land leases in Indonesia.